Morphology, photosynthetic physiology and biochemistry of nine herbaceous plants under water stress - Luo, Qiaoyu; Xie, Huichun; Chen, Zhi; Ma, Yonggui; Yang, Haohong; Yang, Bing; Ma, Yushou (Frontiers in Plant Science, 2023)
Climate warming and shifts in rainfall patterns are expected to trigger frequent and severe drought and waterlogging stress for plants. To cope with water stress, plants develop divergent tactics. However, the adopting capability and mechanisms vary depending upon the plant species and genotype as well as stress duration and intensity. The objectives of this study were to evaluate the species-dependent response of alpine grass species to water stress. Nine grass species were subjected to different levels water stresses (including moderate drought and moderate waterlogging) using a pot experiment based on randomized complete block design with three replications each treatment. We found considerable interspecies differences in plant morphological, physiological traits when plants exposed to the same water regime. Meanwhile, we observed pronounced interactive effects of water regime and species identity on plant height, root length, root/shoot ratio, biomass, contents of chlorophyll a, chlorophyll b, chlorophyll (a+b), carotenoids, malodehyde, soluble sugar, betaine, soluble protein and proline, implying that plants respond to water regime differently. Our finding may cast new lights on ecological restoration of grassland and wetland in Qinghai-Tibetan Plateau by selecting stress-tolerant plant species.